Directional synthesis of liquid higher olefins through catalytic transformation of bio‐oil. Issue 2 (17th July 2013) - Yuan, Yanni; Bi, Peiyan; Fan, Minghui; Zhang, Zhaoxia; Jiang, Peiwen; Li, Quanxin
Abstract BACKGROUND Catalytic transformation of bio‐oil into higher olefins can provide valuable bio‐fuels and chemicals used in the manufacture of high‐octane gasoline, detergents, plasticizers and other petrochemicals. This work explores the production of higher olefins from bio‐oil through catalytic cracking of bio‐oil along with light olefins oligomerization. RESULTS For bio‐oil catalytic cracking, the olefins yield reached 43.8 C‐mol% with near‐complete bio‐oil conversion. The oxygenated organic compounds in bio‐oil go through deoxygenation, cracking and hydrogen transfer reactions and form light olefins over the zeolite acid sites. For the oligomerization of light olefins, the highest selectivity and yield of C5+ olefins over the LTGO catalyst reached 85.4 C‐mol% and 326.7 g kg−1cata h−1, respectively. Main products below 300°C were C6=—C12= olefins, originating from light olefin oligomerization. The influences of the reaction conditions were investigated in detail, and the reaction mechanism was addressed. CONCLUSION Bio‐oil can be catalytically converted to C2=–C4= light olefins over HZSM‐5, and further selectively transformed to C5+ high olefins via the oligomerization of light olefins over LTGO. The transformation of bio‐oil to higher olefins may be useful for the production of bio‐fuels and high value chemicals using renewable biomass. © 2013 Society of Chemical Industry